Cancer therapy with major histocompatibility complex‐deficient and interferon β‐producing myeloid cells derived from allogeneic embryonic stem cells - Umemoto, Satoshi (Cancer Sci, 2019)
We previously established a method to generate myeloid cells with a proliferative capability from pluripotent stem cells and designated them iPS‐ML. Human iPS‐ML cells share features with physiological macrophages including the capability to infiltrate into cancer tissues. We observed therapeutic effects of human iPS‐ML cells expressing interferon β (iPS‐ML/interferon (IFN)‐β) in xenograft cancer models. However, assessment of host immune system‐mediated therapeutic and adverse effects of this therapy is impossible by xenograft models. We currently evaluated the therapeutic effects of a mouse equivalent of human iPS‐ML/IFN, a mouse embryonic stem (ES) cell‐derived myeloid cell line producing IFN (ES‐ML/IFN). The ES‐MLs producing IFN‐β (β‐ML) and IFN‐γ (γ‐ML) and originating from E14 ES cells derived from the 129 mouse strain (H‐2(b)) were generated, and the MHC (H‐2K (b) , D (b) , and I‐A (b)) genes of the ES‐ML/IFN were disrupted using the clustered regularly interspaced short palindromic repeats (CRISPR)/CAS9 method. We used the ES‐ML/IFN to treat allogeneic BALB/c mice (H‐2(d)) transplanted with Colon26 cancer cells. Treatment with β‐ML but not with γ‐ML cells repressed the growth of colon cancer in the peritoneal cavity and liver. The transferred ES‐ML/IFN infiltrated into cancer tissues and enhanced infiltration of T cells into cancer tissues. ES‐ML/IFN therapy increased the number of immune cells in the lymphoid organs. Sensitization of both cancer antigen‐specific CD8(+) T cells and natural killer (NK) cells were enhanced by the therapy, and CD8(+) T cells were essential for the therapeutic effect, implying that donor MHC‐deficient β‐ML exhibited a therapeutic effect through the activation of host immune cells derived from allogeneic recipient mice. The results suggested the usefulness of HLA‐deficient human iPS‐ML/IFN‐β cells for therapy of HLA‐mismatched allogeneic cancer patients.